Arbitration in Theory and Practice: Challenges in Implementing Arbitration in Tulungagung Regency - Neonbeni, Randy Vallentino; Noorhidayah, Noorhidayah; Kariyasa, I Made; Kamri, Andi Khaedhir; Lamsir, Seno; Naufal, Naufal (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
This study examines the disparity between the theoretical framework and practical implementation of arbitration in Tulungagung Regency. Employing an empirical legal approach, the research analyzes data collected from interviews with 12 lawyers and 12 individuals seeking justice. While arbitration offers several advantages, including time efficiency, lower costs, confidentiality, and procedural flexibility, its implementation in Tulungagung Regency encounters significant challenges. The findings indicate that arbitration remains largely unfamiliar to the public, primarily due to limited outreach efforts, the centralized location of arbitration institutions in major cities, and the high fees associated with arbitrators. Furthermore, ambiguities in the enforcement of arbitration decisions and inconsistencies between arbitration rulings and the jurisdiction of certain courts present additional obstacles. These results highlight the necessity for a comprehensive strategy to enhance accessibility and public awareness of arbitration as an effective alternative dispute resolution mechanism.